Pengembangan Profil DPRD Kota Surakarta melalui Video Profile - Yuliana Ningrum, Ervina; Nugroho, Sapto; Tri Vulandari, Retno (Redtech Putra Benua, 2024)
Profile Video as a promotional media and so that it can be better known to the wider community. The data collection method carried out by the author is through field studies, interviews and libraries. This field study was carried out by direct observation at the research location and taking documentation in the form of videos for the needs of making a profile video of the Surakarta DPRD. Then direct interviews are used to improve information in making a profile video of the Surakarta DPRD, while library studies are useful for obtaining related theories based on theories in the form of experts regarding the objects being researched such as applicable laws and regulations and related to the matters being researched. The result obtained is a profile video of the Surakarta DPRD which can support promotional activities and can be better known to the wider community